(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Inhaler is a device holding a medicine taking by breathing (inhalation). It is estimated that about 25 billion dollars spent for inhalers annually, 5-7 billion dollars are wasted because of inhaler misuse. Objective: To evaluate inhaler use technique among Iraqi asthmatic and chronic obstructive pulmonary diseases (COPD) patients and identify the technical mistakes in using inhalers. Methods: The study protocol consisted of interview session to answer the study questionnaire and assessment session to estimate the performance of using inhaler in three cities in the middle of Iraq during the interval between 1st of August and 20th of September 2015. Chi-square test and trend chi-square test were used for univariate association between potential determinants and correctness of inhalation technique. Relevant determinants were entered into a multivariate logistic regression model. Results: A total of 364 patients participated in this study, 39.6% of patients were using their inhalers inadequately. Patients using turbuhaler, older patients (>60 years old) and patients with low level of education or shorter duration of use were significantly associated with more inhaler use mistakes. Conclusion: This study showed that substantial proportion of patients with asthma or COPD using their inhaler inadequately. The worse performance was among patients using turbuhaler and best among those using disckus inhaler. Keywords: Inhaler administration, asthma, COPD, pMDI, turbuhaler, disckus inhaler Citation: Hasanain G. Khudhair, Haidar A.N. Abood, Ali M. Al-Mousawi, Sajjad J. Al-Hatab, Ibrahim A. Al-Obaidi, Ali A.K. Abutiheen. Technical errors in using inhalers among patients with asthma or COPD in Iraq. Iraqi JMS. 2017; Vol. 15(1): 4-12. doi: 10.22578/IJMS.15.1.2